2007
DOI: 10.1016/j.bbrc.2007.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intrarenal oxidative stress and angiotensinogen in IgA nephropathy patients

Abstract: This study was performed to determine whether immunoreactivity of intrarenal hemeoxygenase-1 and angiotensinogen are increased in IgA nephropathy (IgAN) patients. Hemeoxygenase-1 and angiotensinogen immunoreactivity were determined by immunohistochemistry robot system in renal specimens from 39 patients with IgAN. Normal portions of surgically resected kidney served as controls. IgAN patients showed moderate proteinuria (1.1+/−0.2 g/day); however, the control group did not show any proteinuria. Immunoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 54 publications
8
98
0
Order By: Relevance
“…23 In these nephrotic mice, renal AII was increased, although renal renin was suppressed, indicating that a fraction of the Agt that is leaked into Bowman's space is converted to AII and that renal AII content is determined by the intactness of glomerular sieving function to restrict filtration of circulating Agt. Our observations with podocyte disruption echo the earlier findings in patients with glomerular 30 although we found that the origin of Agt is the liver and not the kidney itself. Because renin is also reabsorbed by proximal tubule cells through megalin and ACE is expressed on proximal tubule cells, 23 it is likely that AII is generated within the vicinity where Agt protein is accumulated.…”
Section: Discussionsupporting
confidence: 90%
“…23 In these nephrotic mice, renal AII was increased, although renal renin was suppressed, indicating that a fraction of the Agt that is leaked into Bowman's space is converted to AII and that renal AII content is determined by the intactness of glomerular sieving function to restrict filtration of circulating Agt. Our observations with podocyte disruption echo the earlier findings in patients with glomerular 30 although we found that the origin of Agt is the liver and not the kidney itself. Because renin is also reabsorbed by proximal tubule cells through megalin and ACE is expressed on proximal tubule cells, 23 it is likely that AII is generated within the vicinity where Agt protein is accumulated.…”
Section: Discussionsupporting
confidence: 90%
“…As described previously, we reported that intrarenal AGT immunoreactivity is significantly correlated positively with urinary occult blood, UPro/UCre, and serum creatinine, and correlated negatively with creatinine clearance in IgA nephropathy patients. 24 We do not have any data regarding urinary occult blood or intrarenal AGT immunoreactivity in this study; however, these similar correlation patterns may suggest that urinary AGT levels reflect intrarenal AGT protein levels. In general, the increases in UAlb/UCre, UPro/UCre, and serum creatinine, and the decrease in eGFR represent severity or aggravated renal function in CKD.…”
Section: Single Regression Analysesmentioning
confidence: 57%
“…19-23 We also recently reported that intrarenal AGT immunoreactivity is enhanced in IgA nephropathy patients. 24 Moreover, intrarenal AGT immunoreactivity is significantly correlated positively with urinary occult blood, urinary protein-creatinine ratio (UPro/UCre), and serum creatinine, and correlated negatively with creatinine clearance. 24 Recently, we provided evidence demonstrating that urinary AGT levels reflect intrarenal Ang II activity associated with increased risk for deterioration of renal function in CKD patients.…”
Section: Introductionmentioning
confidence: 98%
“…[20][21][22][23] Many experimental and clinical studies in chronic kidney disease models described possible mechanisms for development of proteinuria via the local RAS in kidney. 9,10,20 Previous studies evaluating the pathogenesis of proteinuria in preeclampsia have demonstrated pathogenic mechanisms including down-regulation of podocyte expression of nephrin, increased endothelin and decreased vascular endothelial growth factor (VEGF), indicating a mechanism where the endothelium loses its fenestrations, an alteration which contributes to protein loss in the urine. [29][30][31][32] Likewise, experimental models demonstrated that locally produced ANG II in the kidney may induce proteinuria via reduction of nephrin expression and podocyte injury and stimulated expression of some cytokines such as VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, urinary AGT was significantly correlated with intrarenal AGT gene expression and ANG II immunoreactivity in patients with normotensive IgA nephropathy. 9 Recent evidence has also revealed that inappropriate activation of intrarenal RAS is an important contributor to the pathogenesis of hypertension and renal injury. [10][11][12] We hypothesized that local RAS activation in the kidneys may have a role in the pathophysiological mechanisms for development of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%